Measurement of Polycyclic Aromatic Hydrocarbons in Baby Food Samples in Tehran, Iran With Magnetic-Solid-Phase-Extraction and Gas-Chromatography/Mass-Spectrometry Method: A Health Risk Assessment - Moazzen, Mojtaba; Shariatifar, Nabi; Arabameri, Majid; Hosseini, Hedayat; Ahmadloo, Mahsa (Frontiers in Nutrition, 2022)
Baby food is one of the most sensitive foods available, which is closely monitored for carcinogens. In this study, 16 Polycyclic Aromatic Hydrocarbon (PAH) compounds were evaluated by using the method of magnetic-solid-phase-extraction and gas-chromatography/mass-spectrometry (MSPE/GC-MS). The recovery, limit of detection (LOD), and limit of quantification (LOQ) of PAH compounds were 93.4–101.6%, 0.06–1.12, and 0.18–3.38 μg/kg, respectively. The results indicated the mean of total PAHs in all samples was 3.73 ± 0.8 μg/kg, and the mean of Benzo[a]pyrene (BaP) was 0.29 ± 0.14 μg/kg that were lower than the USA-Environmental Protection Agency (USEPA) standard level (1 μg/kg, BaP in baby foods). In addition, our results showed that mixed five cereal-based baby food had a maximum mean of ΣPAHs (5.06 ± 0.68 μg/kg) and mixed wheat and date-based baby food had a minimum mean of ΣPAHs (3.03 ± 0.41 μg/kg). The carcinogenic risk due to PAH in the tested baby foods sold in Iran was adequately low, and all examined products were safe for consumers. Therefore, it can be said that the consumption of baby foods does not pose a threat to consumers.